The Oxford Handbook of Assessment Policy and Practice in Music Education, Volume 1 2019
DOI: 10.1093/oxfordhb/9780190248093.013.25
|View full text |Cite
|
Sign up to set email alerts
|

Developing Tests of Music Performance Improvisation

Abstract: This chapter presents a survey of research on the development and validation of a measure to assess instrumentalists’ ability to improvise music. It begins by framing efforts to distinguish between visual, aural, and creative forms of music performance, and the types of assessment tasks required to evaluate music performance improvisation. The chapter surveys a range of related measures that have been used to assess improvisational abilities in young developing musicians and provides a detailed description of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…A study by Anderman and Maehr (2014) found that students who had positive experiences with music, such as participating in choirs or playing instruments, showed a higher level of interest in music theory. Prior exposure to music performance and active engagement in making music create a foundation for students to appreciate and understand music theory concepts (McPherson & Welch, 2018). Effective teaching methods play a crucial role in nurturing student interest in music theory.…”
Section: Enhancing the Interest Of Colleges Of Education Students In ...mentioning
confidence: 99%
“…A study by Anderman and Maehr (2014) found that students who had positive experiences with music, such as participating in choirs or playing instruments, showed a higher level of interest in music theory. Prior exposure to music performance and active engagement in making music create a foundation for students to appreciate and understand music theory concepts (McPherson & Welch, 2018). Effective teaching methods play a crucial role in nurturing student interest in music theory.…”
Section: Enhancing the Interest Of Colleges Of Education Students In ...mentioning
confidence: 99%